2015
DOI: 10.1002/jclp.22204
|View full text |Cite
|
Sign up to set email alerts
|

Integration of e‐Health Tools Into Face‐to‐Face Psychotherapy for Borderline Personality Disorder: A Chance to Close the Gap Between Demand and Supply?

Abstract: Borderline personality disorder (BPD) is a severe, highly prevalent mental disorder. Effective psychological treatments for BPD are available. However, most patients do not receive evidence-based treatments partly because of high treatment delivery costs and lack of specialized therapists. By integrating specialized e-health tools into BPD-specific treatments, treatment intensity can be increased, frequency of face-to-face sessions and burden for psychotherapists can be reduced, and implementation of new skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…This study emerged from a pilot study concerning the feasibility and safety of priovi in conjunction with face-to-face ST at the Department of Psychiatry and Psychotherapy, University of Lübeck, Germany, in cooperation with GAIA AG (Hamburg, Germany), the company that developed priovi [ 15 , 20 ]. Approval was granted by the Ethics Committee of the University of Lübeck (AZ 14-038).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study emerged from a pilot study concerning the feasibility and safety of priovi in conjunction with face-to-face ST at the Department of Psychiatry and Psychotherapy, University of Lübeck, Germany, in cooperation with GAIA AG (Hamburg, Germany), the company that developed priovi [ 15 , 20 ]. Approval was granted by the Ethics Committee of the University of Lübeck (AZ 14-038).…”
Section: Methodsmentioning
confidence: 99%
“…Priovi also provides some other features like a glossary explaining the most important terms around BPD and ST or a “mode toolbox” where exercises can be stored and revisited. A more detailed description of priovi can be found elsewhere [ 15 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies including the use of eHealth, warrant further exploration, though current evidence of their effectiveness is promising (Kudlow 2013). For example, in a pilot study of a BPD eHealth tool that provides tailored communication and education through messages and activities, Fassbinder et al (2015) reported a significant decrease in BPD-related symptoms after 6 months of usethough more rigorous testing is required to determine true effectiveness. Furthermore, urgent care facilities for psychiatric needs provide a safe alternative to ED care for patients experiencing acute and persistent psychiatric symptoms.…”
Section: Falling Through the Cracksservices That Do Not Workmentioning
confidence: 99%